Evaluating the Implementation of fan-beam CT-guided online adaptive re-planning in definitive cervical cancer radiotherapy - Sun, Shuai; Gong, Xinyue; Liang, Yongguang; Sun, Yuliang; Que, Dan; Xie, Yangchun; He, Shumeng; He, Lei; Liang, Hao; Wang, Yijun; Wu, Xinyi; Wang, Cheng; et al. (Frontiers in Oncology, 2025)
BackgroundThis study aims to investigate the feasibility of fan-beam computed tomography (FBCT)-guided online adaptive radiotherapy (oART) in radical radiotherapy for cervical cancer.MethodsTen patients who underwent radical radiotherapy for cervical cancer were enrolled in this study. All patients received external beam radiation therapy (EBRT) with a prescription dose of 50.4 Gy/28f, and daily oART with FBCT guidance was performed. Dosimetric analysis was conducted on 278 fractions, comparing the adaptive and scheduled plans. The γ passing rate was measured through in-vivo dose monitoring during treatment, using a 3%/3mm gamma criterion with an 88% threshold for alerts. The time invested in the oART workflow was recorded at each step. Acute toxicities were classified following the Common Terminology Criteria for Adverse Events (CTCAE) version 5.0.ResultsThe adaptive plans demonstrated a dosimetric advantage in target coverage and/or organs at risk (OARs) sparing across all 278 fractions. Compared to the scheduled plan, the adaptive plan showed improved dose received by 95% (D95) of planning target volume (PTV), conformity index (CI), and homogeneity index (HI) (P<0.001). Among the three PTVs, the PTV of uterus (PTV_U) benefited most from dosimetric improvements in the adaptive plan, followed by the PTV of cervix, vagina, and parametrial tissues (PTV_C), while the PTV of lymph node (PTV_N) exhibited the least enhancement. For OARs, the adaptive plan achieved reductions in the dose to the most irradiated 2 cm³ volume (D2cc) for the rectum, bladder, and small intestine (P<0.001). For patients with ovarian conservation, the dose to the 50% volume (D50) and the mean dose of the bilateral ovaries were decreased (P<0.001). The mean γ passing rate across all fractions was 99.24%. The mean duration of the oART workflow was 22.82 ± 3.61 min, with auto-segmentation & review (44.40%) and plan generation & evaluation (22.02%) being the most time-intensive steps. The incidence of Grade 1-2 acute non-hematological toxicity was 60%, with no cases of Grade 3 or higher observed.ConclusionsThe implementation of FBCT-guided oART in radical radiotherapy for cervical cancer was feasible. This approach has shown significant improvements in dose distribution and the potential to provide clinical benefits by reducing acute toxicity.